Pengaruh Ketebalan Mulsa Organik Kirinyuh (Chromolaena odorata) terhadap Pertumbuhan Rumput Mulato (Brachiaria hybrid cv. Mulato) - Kore, Melani Juita Titu; Nastiti, Herayanti Panca; Osa, Dominggus B. (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this research was to determine using Kirinyuh (Chromolaena odorata) organik mulch thickness on growth Brachiaria hybrid cv. Mulato. The material used in the form of organic mulch for Chromolaena odorata, grass pols, Brachiaria hybrid cv. Mulato. The research used a Completely Randomized Design (CRD) with 4 treatments and 4 replications, a total of 16 experimental units. These treatments are: M0: without mulch, M1 thickness : 1 cm, M2 thickness: 3 cm, M3 thickness: 5 cm. The variables studied were plant height, number of tillers, and number of leaves. Data were analyzed using analysis of variance (ANOVA) and Duncan's advanced test. The results of analysis of variance (ANOVA) showed that the treatment had a significant effect (P<0.05) on plant height, number of tillers, and number of grass leaves Brachiaria hybrid cv. Mulato. Duncan's test results showed that between treatments M0:M1, M0:M2, M0:M3 significant different (P<0.05) and between treatments M1; M2; M3 not significant different (P>0.05) on plant height, number of tillers and number of leaves Brachiaria hybrid cv. Mulato. The conclusion is that the application of organic mulch Kirinyuh (Chromolaena odorata) affects the growth performance of Mulato grass plants (Brachiaria hybrid cv. Mulato) the best performance was obtained in M2 namely plant height (34.79cm), number of tillers (22.88 tillers) and number of leaves (100.15) strands.